Meningkatkan Hasil Belajar Siswa Dalam Keterampilan Menulis Puisi Pada Mata Pelajaran Bahasa Indonesia Dengan Penggunaan Pendekatan Contextual Teaching And Learning Di Kelas V SDN 1 Parahiang Lebak Banten - Agus Agung Gumelar; Ratna Dewi; Rifki Arif Nugraha (Desanta Publisher, 2023)
This study aims to describe the process and results of learning Indonesian in improving the poetry writingskills of fifth grade students at SDN 1 Parahiang through the Contextual Teaching and Learning (CTL)approach. This type of research is Classroom Action Research (CAR) with the John Elliot model. The stepstaken include planning, action, observation and reflection.The subjects of this research were 29 students of V Sdn 1 Parahiang Lebak Banten. This research wasconducted in 2 cycles. Each cycle consists of 1 meeting. Data collection techniques used are tests,observations, and documentation. The results showed an increase in student learning outcomes. In the preaction test the average value was 63.28 while in the first cycle the average value reached 78.66. Thus theincrease in the average value of writing poetry from pre-action to cycle I was 15.38 points. In cycle II theaverage score reached 84.72 which increased by 6.06 points from cycle I and 21.44 points from the preaction test. From the results obtained, it can be concluded that the Contextual Teaching and Learning(CTL) approach can improve student learning outcomes. Based on the research results, teachers areadvised to apply the use of the Contextual Teaching and Learning (CTL) approach because it is proven toimprove student learning outcomes.